Spontaneous Plants Improve the Inter-Row Soil Fertility in a Citrus Orchard but Nitrogen Lacks to Boost Organic Carbon - Visconti, Fernando; Peiró, Enrique; Baixauli, Carlos; De-Paz, José M. (MDPI, 2023)
The inter-row soils in conventionally run citrus orchards in Eastern Spain lose fertility, either physically, chemically, or biologically, as a consequence of machinery traffic and the use of herbicides. In order to regain inter-row soil fertility, two grass-cover management alternatives to the commonly used herbicide-kept bare management, namely, spontaneous plants and fescue, were established and left for four years until their effects on several physical, chemical, and biological parameters were monitored for two years more. The fescue ground cover exhibited lower average and maximum soil temperatures due to higher evapotranspiration rates but also higher annual soil water content on average and, additionally, higher rhizodeposition. Despite the fact that these new beneficial conditions helped enhance the soil’s biological fertility under fescue, the physical or chemical fertilities did not improve and neither did the organic carbon (SOC). The spontaneous plants also enhanced the biological fertility, but in this case, beneficial conditions were reflected by improvements in the chemical fertility, particularly the exchangeable potassium, and in the physical fertility by increasing the surface hydraulic conductivity and decreasing the bulk density. In the inter-rows of this citrus orchard, a seeded grass cover does not seem able to provide any soil fertility enhancement in comparison to a spontaneous one; rather the opposite. However, a lack of natural or man-driven nitrogen inputs poses a constraint to SOC gains. For this aim, the annual surface application of organic nitrogen-rich materials or even better, the fostering of N-fixing organisms would be recommended.